2019
DOI: 10.1152/ajpendo.00553.2018
|View full text |Cite
|
Sign up to set email alerts
|

mTORC1/rpS6 signaling complex modifies BTB transport function: an in vivo study using the adjudin model

Abstract: Studies have shown that the mTORC1/rpS6 signaling cascade regulates Sertoli cell blood-testis barrier (BTB) dynamics. For instance, specific inhibition of mTORC1 by treating Sertoli cells with rapamycin promotes the Sertoli cell barrier, making it “tighter.” However, activation of mTORC1 by overexpressing a full-length rpS6 cDNA clone (i.e., rpS6-WT, wild type) in Sertoli cells promotes BTB remodeling, making the barrier “leaky.” Also, there is an increase in rpS6 and p-rpS6 (phosphorylated and activated rpS6)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 84 publications
0
16
0
Order By: Relevance
“…via oral gavage markedly enhanced adjudin uptake, reflecting a 'leakier' BTB [33], under conditions where adjudin alone at 10 mg/kg b.w. did not affect BTB function in vivo [33,34], and only acute doses of adjudin (125 or 250 mg/kg b.w.) induced irreversible BTB damage and caused infertility [64].…”
Section: Modulating Rps6mentioning
confidence: 85%
See 4 more Smart Citations
“…via oral gavage markedly enhanced adjudin uptake, reflecting a 'leakier' BTB [33], under conditions where adjudin alone at 10 mg/kg b.w. did not affect BTB function in vivo [33,34], and only acute doses of adjudin (125 or 250 mg/kg b.w.) induced irreversible BTB damage and caused infertility [64].…”
Section: Modulating Rps6mentioning
confidence: 85%
“…In vivo studies in the testis have shown that testicular cells, most notably Sertoli cells, produce several biologically active peptides through proteolytic cleavage of constituent proteins at the apical ES and basement membrane ( Figure 2) during spermatogenesis, and these peptides can effectively modulate the organization of the Sertoli cell cytoskeleton and hence BTB structure, function, and spermatogenesis through downstream signaling proteins [31]. Because these biologically active molecules modulate the BTB function, they can facilitate the transport of drugs across the BTB, as shown in studies that used a candidate non-hormonal male contraceptive drug, adjudin [32][33][34]. We discuss below these peptides and present a hypothetical model in which the activity of these peptides and associated signaling molecules can alter the BTB permeability barrier function to support the transport of developing germ cells, namely preleptotene spermatocytes, across the BTB during spermatogenesis ( Figure 2).…”
Section: Overview Of the Blood-testis Barriermentioning
confidence: 99%
See 3 more Smart Citations